An Assessment of Climate Change Mitigation via Location Specific Climate Smart Horticulture: A Review Paper (International Journal of Innovative Research in Engineering & Management, 2023)
The first stage in preparing the  horticulture industry for creating adaptation plans under  climate change scenarios is to quantify the effects of  temperature fluctuations, surplus and restricted moisture  conditions. Individual crop effects have been studied and  assessed throughout the main agro-ecological areas and  growing seasons. Scientific validation is required for  production methods that may be modified to adapt for  climate change. Although production regions for particular  crops or the time of sowing and planting may be altered the  markets windows as well as infrastructure, like the  availability of local packaging as well as the distribution  facilities, are important components to consider for many  horticultural commodities. It's expected to change key  interactions among horticultural plants as well as  pollinators, insects, disease, pests, weeds, pests as well as weeds. Because horticulture-based agricultural systems  offer a great potential for sequestering carbon for climate  change mitigation, there is a need for a fast and clear  knowledge of the effect of climate change on horticultural  crops in order to develop a solid action plan. Perennial tree work as carbon sinks by sequestering carbon from the  atmosphere. The clean development method may be used  to get the carbon credits. Based on location-specific  climate smart horticulture concepts, an integrated strategy  with all available choices will be most successful in  maintaining production under climate change  circumstances.
Keywords: Climate change; Horticultural crops; Location specific research; Smart Horticulture